China's rise: The return of geopolitics? - Gudrun Wacker (Stiftung Wissenschaft und Politik (SWP), 2006)
The "rise of China," like hardly any other topic, feeds speculation about the future of the international system and its structures, the global economy, and energy security. Whether the ascent of the last couple of years can simply be extrapolated, and how strong China's economy already is in comparison to other powers, may be matters of debate. But there can be no doubt that China's increasing economic might, its political standing in Asia and other continents, and the possibility of superpower rivalry between China and the United States are of eminent significance for German and European politics and will not leave Europe's relations with the United States untouched either.The symposium on "China's Rise: The Return of Geopolitics?" that was held on January 18, 2006 at the German Institute for International and Security Affairs (Stiftung Wissenschaft und Politik) focused on China's reach into other regions of the world. China's domestic development, in particular the questions of a possible end of the economic boom, problems that might arise through growing social inequalities, and whether oneparty rule can be reconciled with a market economy in the medium term were not the subject of this event. Instead, we turned the spotlight on the international dimension of China's growing importance, not least the new economic giant's search for energy supplies, resources, and political influence.We have issued the resulting papers in German and English without a great deal of editorial and academic reworking, in the interests of speed of publication. We would like them to be seen as a contribution to the debate and as a part of the SWP's ongoing research program
Keywords: 320